2023
DOI: 10.3389/fimmu.2023.1053550
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic immunomodulation by rationally designed nucleic acids and nucleic acid nanoparticles

Abstract: The immune system has evolved to defend organisms against exogenous threats such as viruses, bacteria, fungi, and parasites by distinguishing between “self” and “non-self”. In addition, it guards us against other diseases, such as cancer, by detecting and responding to transformed and senescent cells. However, for survival and propagation, the altered cells and invading pathogens often employ a wide range of mechanisms to avoid, inhibit, or manipulate the immunorecognition. As such, the development of new mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 131 publications
(168 reference statements)
0
7
0
Order By: Relevance
“…In our study, we conduct a series of experiments to assess whether DNA triangles with various ssT regions would elicit an immune response or prove to be toxic to human cells. We utilize three different reporter cell lines (HEK-Blue hTLR7, HEK-Blue hTLR9, and HEK-Lucia RIG-I) engineered to turn up the activation of specific pathways related to the detection of exogenous nucleic acids. While TLR9 is a well-known key receptor for the recognition of DNA, TLR7 primarily recognizes ssRNAs. However, it has been reported that TLR7 also has the ability to respond to deoxyguanosine, independent of RNA. , Furthermore, recent studies have indicated the possible recognition of DNA nanoparticles by TLR7 .…”
Section: Resultsmentioning
confidence: 99%
“…In our study, we conduct a series of experiments to assess whether DNA triangles with various ssT regions would elicit an immune response or prove to be toxic to human cells. We utilize three different reporter cell lines (HEK-Blue hTLR7, HEK-Blue hTLR9, and HEK-Lucia RIG-I) engineered to turn up the activation of specific pathways related to the detection of exogenous nucleic acids. While TLR9 is a well-known key receptor for the recognition of DNA, TLR7 primarily recognizes ssRNAs. However, it has been reported that TLR7 also has the ability to respond to deoxyguanosine, independent of RNA. , Furthermore, recent studies have indicated the possible recognition of DNA nanoparticles by TLR7 .…”
Section: Resultsmentioning
confidence: 99%
“…30−32 Notably, TLR3 is highly expressed in many types of human solid tumors, including lung and breast cancer, oral cell squamous carcinoma, cervical carcinoma, and head and neck carcinoma. 33,34 This receptor is located in intracellular cytoplasm or endosomes and sensed double-stranded RNA (dsRNA) viruses, including polyriboinosinic:polyribocytidylic acid (poly (I:C)). 35−37 TLR3 signaling activates NF-κB and upregulates the RHCG gene.…”
Section: Introductionmentioning
confidence: 99%
“…The toll-like receptors (TLRs) are critical in innate immunity as pattern recognition receptors. TLR3 is predominantly expressed in innate immune cells, such as dendritic cells (Figure S1), macrophages, and natural killer cells, which have been exploited extensively to enhance an antitumor immune response. Notably, TLR3 is highly expressed in many types of human solid tumors, including lung and breast cancer, oral cell squamous carcinoma, cervical carcinoma, and head and neck carcinoma. , This receptor is located in intracellular cytoplasm or endosomes and sensed double-stranded RNA (dsRNA) viruses, including polyriboinosinic:polyribocytidylic acid (poly (I:C)). TLR3 signaling activates NF-κB and upregulates the RHCG gene.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, fibrous materials offer a large surface area, allowing the delivery of a more significant number of functional moieties than a spherical nanocarrier may offer. Moreover, a nonspherical shape has been suggested to improve the vascular transport of nanomaterials and therapeutic cargo delivery into the interstitial space. , To leverage these benefits of fibrous shape while avoiding undesirable inflammatory responses, researchers turned their attention to “soft” and biodegradable materials such as those made of natural RNA and DNA biopolymers. The field of nucleic acid nanoparticles (NANPs) is fast growing and has already demonstrated numerous beneficial, safe, and environmentally friendly applications ranging from therapeutic indications as nanomedicines to the use as structural components of light-emitting diodes, functional photonic devices, and biosensors. …”
mentioning
confidence: 99%
“…All previous studies investigating structure–activity relationships (SAR) between NANPs physicochemical properties and cytokine responses employed globular and planar architectures of NANPs, such as cubes and rings, respectively. While fibrous NANPs were studied, due to their lower immunostimulatory potential as compared to cubes and rings, they were used as controls demonstrating that shape contributes to the immunorecognition of intracellularly delivered NANPs. , However, the SAR of design elements that may contribute to the immunorecognition of intracellularly delivered fibers has never been investigated thoroughly. Therefore, the present work expands on previously published studies by investigating the role of the engineering design and physicochemical properties of fibrous NANPs in their immunorecognition.…”
mentioning
confidence: 99%